Relationship between the Metaphor Perception and School Climate on the Profession of Nursing Students (Bangladesh Journal of Medical Science, 2021)
Aim: The aim of this study was to determine the effects of the school climate on nursing seniorstudents on the perception of metaphor for nursing.Method: Sample of the study was formedwith volunteer students (n = 130) to participate in the study on the date of the data collection.In the evaluation of quantitative data, frequency, percentage, mean, independent sample t-test,and in the evaluation of qualitative data content analysis methods were used. The categories inwhich including the positive and negative metaphors in the study are constructed in five differentways (vital, object, struggle, abstraction, productivity). The primary metaphors are being beenthe mother, the angel, the medicine and the robot.When the metaphors were examined, a vitalexpression of vast majority has been seen as the nursing perception.Result: When the students’metaphor perceptions were compared with school climate scores, it was found that there was asignificant relationship between them (t=2.259, p=.026). Metaphors have provided an indicationof the produced individual perception on the nursing profession.Conclusion:Metaphors can beused as a powerful research tool to reveal to what extent students’ school climate influencesthese metaphors.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.107-114